1988
DOI: 10.1097/00000658-198807000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis-induced Acute Lung Injury

Abstract: Cerulein-induced acute pancreatitis in rats is associated with acute lung injury characterized by increased pulmonary microvascular permeability, increased wet lung weights, and histologic features of alveolar capillary endothelial cell and pulmonary parenchymal injury. The alveolar capillary permeability index is increased 1.8-fold after a 3-hour injury (0.30 to 0.54, p less than 0.05). Gravimetric analysis shows a similar 1.5-fold increase in wet lung weights at 3 hours (0.35% vs. 0.51% of total body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…The dose chosen was in excess of that required to stimulate a maximal rate of digestive enzyme secretion from the pancreas. Supramaximal secretagogue stimulation of the pancreas with caerulein is known to cause acute pancreatitis characterized by initial pancreatic inflammation and acinar cell necrosis (9) followed by a secondary respiratory distress syndrome associated with hypoxemia, hypercarbia, and PMN sequestration in the lung (7,8). Previous studies have suggested a role for complement, neutrophils, and TNF in this response (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose chosen was in excess of that required to stimulate a maximal rate of digestive enzyme secretion from the pancreas. Supramaximal secretagogue stimulation of the pancreas with caerulein is known to cause acute pancreatitis characterized by initial pancreatic inflammation and acinar cell necrosis (9) followed by a secondary respiratory distress syndrome associated with hypoxemia, hypercarbia, and PMN sequestration in the lung (7,8). Previous studies have suggested a role for complement, neutrophils, and TNF in this response (10).…”
Section: Resultsmentioning
confidence: 99%
“…A linkage between the cytokine (e.g., TNF-␣ ) and chemokine systems in the genesis of these syndromes may be postulated. In rodents, a model of these processes dependent on the initiation of acute pancreatitis has been well described (7,8). After overstimulation of pancreatic exocrine acinar cells with the cholecystokinin analogue caerulein, pancreatic injury occurs that is characterized by edema, leukocyte influx into the pancreas, and elevated levels of pancreatic enzymes in the serum (9).…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of the bacterial cell wall in vivo releases LPS into the body fluids resulting in activation of various cellular and humoral mediators of inflammation, such as cytokines and reactive oxygen species (ROS), which may result in septic shock and multi-organ dysfunction and failure [2, 3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Several models of acute pancreatitis in experimental animals have been shown to be accompanied by measurable lung injury (9,14,15,37), and a number of recent studies have focused on identifying the factors that couple pancreatic inflammation to lung injury in those models (1,2,10,26). In the current communication, we have utilized the secretagogue (caerulein)-induced model of acute pancreatitis (20) in mice to examine the role played by granulocyte-macrophage colony-stimulating factor (GM-CSF) in mediating acute lung injury in this model.…”
mentioning
confidence: 99%